Kajian Karakteristik Gelombang Laut di Wilayah Pantai Pulau Merah, Kabupaten Banyuwangi - Khairunnisa, Anggareta; Kristianto, Aries (Journal of Marine Research and Technology; Vol 6 No 2 (2023): AGUSTUS 2023, 2023)
Sea wave parameter information is used in maritime-related activities such as sea transportation, offshore exploration, fisheries, port construction, shipping safety, coastal area development, and coastal mitigation. This study described the characteristics of the sea waves in Pulau Merah Beach, Banyuwangi Regency. Wind reanalysis data of 10 meters was processed using the Sverdrup Munk Bretschneider (SMB) method using the Easywave algorithm. The analyzed and processed the sea wave model's assimilation data from Marine Copernicus pointwise by WRPLOT. The results of wind and ocean wave data processing showed that the direction, height, and period of sea waves on Pulau Merah Beach are strongly influenced by the Monsoon Wind. The sea wave height in the Pulau Merah Beach region reaches its peak value during the East season, which is 1.5 meters. In contrast, the value of the period of sea waves in the Pulau Merah Beach area reached its peak value during the Transitional Season I period, which was 8.3 seconds.